The effects of forced exhalation and inhalation, grunting, and valsalva maneuver on forehand force in collegiate tennis players - O'Connell, D. G.; Brewer, J. F.; Man, T. H.; Weldon, J. S.; Hinman, M. R. (The Journal of Strength and Conditioning Research, 2016)
To examine the effects of forced expiration (FE), forced inspiration (FI), grunting (GR), and valsalva maneuver (VM), on air volume, maximum force production, and muscle recruitment during a simulated forehand stroke in collegiate tennis players. Superficial electrodes were placed over the anterior deltoid, pectoralis major, rectus abdominis, lumbar and thoracic erector spinae, and external and internal obliques. Subjects stood in a simulated forehand stroke stance with their dominant hand positioned on a force plate. Subjects performed 3 repetitions of maximal 2- to 3-second isometric forehands with randomly assigned breathing conditions (FE, FI, VM, and GR) and 30-seconds rest between contractions. Air volumes were also collected during each trial. A repeated-measures multivariate analysis of variance compared normalized peak electromyographic activity across the 7 muscle groups. Separate repeated measures ANOVAs compared the effect of breathing conditions on peak force production and air volume. Statistical significance was set at p = 0.05 for all analyses. Overall muscle activity differed significantly by breathing condition (p = 0.031) with greater anterior deltoid activity was seen in FE and GR vs. VM. Internal oblique activity was significantly greater in GR than FI or VM, and thoracic erector spinae activity was significantly greater during FE and VM than FI. Force production did not differ significantly among breathing conditions (p = 0.74); however, GR forces were greater than FI and VM forces (p = 0.05). Forced expiration air volume was significantly greater (p < 0.001) than FI, GR, or VM. These findings suggest that either GR or a more quiescent FE can be used to enhance force production. Forced expiration is a potentially safer alternative to VM and more aurally pleasing than GR.